2010
DOI: 10.9755/ejfa.v22i2.4900
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed priming on germination and seedling growth of two medicinal plants under salinity

Abstract: Priming is one of the seed enhancement methods that might be resulted in increasing seed performance (germination and emergence) under stress conditions such as salinity, temperature and drought stress. The objective of this research was to evaluate the effect of different priming types on seed germination of two medicinal plants including pot marigold (Calendula officinalis) and sweet fennel (Foeniculum vulgare) under salinity stress. Treatments were combinations of 5 levels of salinity stress (0, 2.5, 5, 7.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
46
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 20 publications
7
46
1
2
Order By: Relevance
“…The beneficial aspects of SA are that it could be used for the improvement of salt bearing capacity of many crops. Sedghi et al, (2010) results indicated that with increasing salinity, germination traits such as germination percent, rate and plumule length decreased, but seed priming with GA3 and NaCl showed lower decrease. In all of the salinity levels, primed seeds possessed more germination rate and plumule length than control.…”
mentioning
confidence: 91%
“…The beneficial aspects of SA are that it could be used for the improvement of salt bearing capacity of many crops. Sedghi et al, (2010) results indicated that with increasing salinity, germination traits such as germination percent, rate and plumule length decreased, but seed priming with GA3 and NaCl showed lower decrease. In all of the salinity levels, primed seeds possessed more germination rate and plumule length than control.…”
mentioning
confidence: 91%
“…Similarly, Cano et al (1991) reported that fruit yield was greater in tomato plants derived from NaCl primed seeds than from non-primed ones when grown under saline conditions. The effect of NaCl priming is greater when salt treatment was applied at germination than when applied at seedling stage (Sedghi et al, 2010). The effect of seed priming on growth and yield have rarely been studied in many plants including maize (Foti et al, 2008).The present study investigate the effect of seed priming with NaCl on the growth and yield of two maize cultivars when subsequently exposed to salinity.…”
Section: Introductionmentioning
confidence: 96%
“…One of the important strategies for increasing germination speed and germination percentage, to produce high quality seedling and plant optimal establishment is seed priming [2]. Priming is one of the seed enhancement methods that might be resulted in increasing seed performance (germination and emergence) under stress conditions [3]. Various seed priming techniques have been established and the best low cost methods like hydro-priming, priming with plant growth regulators, osmo-priming, solid matrix-priming, and bio-priming are practiced by framers in fields [4].…”
Section: Introductionmentioning
confidence: 99%